PERANCANGAN INTERFACE MOBILE START UP â€œSERVICE INâ€ MENGGUNAKAN METODE DESIGN THINKING DAN ANALISIS GSTALT - Lubis, Hendarman; Harun, Rofiq; Rahma, Dea Wemona; Satrinia, Dwina (STMIK BINA PATRIA, 2025)
The development of digital technology has encouraged the emergence of various mobile application-based services to facilitate daily activities. The Service In application is present as a digital start-up solution that provides online technician booking services via mobile devices. The development method used in this study is the Design Thinking Method which consists of the stages of Empathize, Define, Ideate, Prototype and Test. The GSTALT principle consisting of; Proximity, Similarity, Common-region, Focal point, Continuity, Closure and Figure/ground is used in designing the user interface of the